Jessa Murphy: capstone - Murphy, Jessa, artist (Colorado State University. Libraries, 2014)
The artist's statement: The most persistent challenge and intriguing venture in graphic design has been to create an image simple enough to speak a multitude of words while remaining visually entertaining. I have most enjoyed finding a solution to this challenge while designing logos and accompanying branding as well as when designing advertisements. Stylistically, the graphic design I enjoy creating most is a wonderful matchup of opposites. I enjoy creating a collage of various mediums in a tasteful way. Hand drawn elements for example, lend authenticity to a piece because they are unique to each artist but when they are paired with geometric shapes or a very clean typeface, organization is achieved. A fundamental concept I have learned that continues to be influential to my design is to consistently find new ways to maintain a unique design style. When presented the opportunity to create an image that will embody an overarching idea, I have found it useful to conduct searches of common representations of this idea in order to stay away from overused images in my own design. Another profound learning experience for me has been to take a motion graphics class where I learned the beauty and functionality of sending a message in the form of time based or video art piece. Going forward, I will continue to create learning experiences for myself in the realm motion graphics creation to make websites and advertisements come to life and have greater user interface. I also strive to advance my skill set in the creation of original textures and brushes in a way that will lend itself to my passion for mixed media. In addition, I look forward to continuing progression in digital photography shooting and editing as well as with hand lettering. I hope to combine all of these passions and learning experiences to create promotional materials that will advance the objectives of organizations benefitting consumers, society, and the environment.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.